A Study on Privacy Preservation Techniques and Scope of Applying Deep Learning Concepts in Security: a Survey - Arun Kumar, Ravula; Vinuthna Kambalapally, Dr (International Journal of Engineering and Technology, 2018)
The Data privacy and security plays a major scientific role in the research industry with a variety of content and with different datasets of cloud â€“fog â€“ Internet of things. These three domains have been placed a rapid search content in security as well as networking basics. Here, it is found that different survey methods and search techniques that provides secure privacy data when data gets uploaded to the cloud via fog nodes. Thus, we also check those can be any deep learning techniques that can be applied for the purpose of security in cloud source.Â Infrastructure as the fog computing is named as edge computing which has a disturbed network, so it canâ€™t be entirely trusted when we upload the data to the cloud and in fact, cloud also has some concerns about security as it is updated and maintained by third party service providers. To precise, we check various methods that can be applied to secure the data, make comparisons and also checking for the crop where can be deep neural learning along with machine learning can be applied for this survey.Â Â